In vivo wound healing activity of electrospun nanofibers embedding natural products - Breno de Almeida Bertassoni; Denise de Abreu Garófalo; Mariana Sato de Souza Bustamante Monteiro; Ralph Santos-Oliveira; Anne Caroline Candido Gomes; Anna Lecticia Martinez Martinez Toledo; Marcos Lopes Dias; Naomi Kato Simas; Eduardo Ricci-Junior (Arabian Journal of Chemistry)
Nanofibers are threads at the nanometric scale. Electrospinning is a technique that uses electric fields as the driving force to produce fibers ranging from nanometers to micrometers. Membranes based on polymeric nanofibers obtained through electrospinning possess an excellent capacity to carry drugs and natural active components, promoting skin healing and regeneration in various ways. Natural products derived from plants have gained attention in recent decades due to their accessibility, good biocompatibility, biodegradability, and incorporation into nanofibers. These products can influence multiple stages of the healing process and exhibit antimicrobial activity, thereby preventing and combating infections. Consequently, the combination of natural products and nanofibers presents a promising approach to infection prevention and skin wound healing. In this context, the current paper presents a systematic literature review of studies conducted from 2011 to 2024. It focuses on articles concerning the production of nanofibers via electrospinning that embed active components of natural origin, specifically those that performed in vivo tests to assess wound healing potential. A total of 26 articles met the inclusion criteria and were analyzed in terms of production and characterization of the electrospun membranes using in vitro and in vivo tests. Most studies employed a mixture of polyvinyl alcohol (PVA) with another polymer, utilized plant extracts like Malva sylvestris as active components, and performed in vitro tests using fibroblasts. Antimicrobial tests were conducted against Staphylococcus aureus and Escherichia coli, while male Wistar rats were used in excision/incision wound models for in vivo tests. The results indicate that natural products influence the properties of the scaffolds in different ways, such as increasing fiber diameter and mechanical strength, and may also accelerate wound healing.